Insights into Key Challenges of the Albanian Labor Market - Dávalos, María E.; Cancho, César (World Bank, Washington, DC, 2015)
This note presents an overview of the Albanian labor market, and initial insights into the challenges for inclusive and better quality jobs. The note does not intend to be comprehensive, but rather aims at compiling – under an integrative jobs umbrella and the regional framework on jobs – some of the available data and evidence on the Albanian jobs challenge, part of which was prepared for the Albania Systematic Country Diagnostic of the World Bank. By employing the regional report’s framework, the note can guide the Government, development partners, civil society and other stakeholders in identifying the many knowledge gaps that remain for a comprehensive jobs agenda and the work needed towards completing the picture.